Development and Interpretation of Multiple Machine Learning Models for Predicting Postoperative Delayed Remission of Acromegaly Patients During Long-Term Follow-Up - Dai, Congxin; Fan, Yanghua; Li, Yichao; Bao, Xinjie; Li, Yansheng; Su, Mingliang; Yao, Yong; Deng, Kan; Xing, Bing; Feng, Feng; Feng, Ming; Wang, Renzhi (Frontiers in Endocrinology, 2020)
Background: Some patients with acromegaly do not reach the remission standard in the short term after surgery, but achieve remission without additional postoperative treatment during long-term follow-up; this phenomenon is defined as postoperative delayed remission (DR). DR may complicate the interpretation of surgical outcomes in patients with acromegaly, and interfere with decision-making regarding postoperative adjuvant therapy. Objective: We aimed to develop and validate machine learning (ML) models for predicting DR in acromegaly patients who have not achieved remission within 6 months of surgery. Methods: We enrolled 306 acromegaly patients, and randomly divided them into training and test datasets. We used the recursive feature elimination (RFE) algorithm to select features, and applied six ML algorithms to construct DR prediction models. The performance of these ML models was validated using receiver operating characteristics analysis. We used permutation importance, SHapley Additive exPlanations (SHAP), and local interpretable model–agnostic interpretation (LIME) algorithms to determine the importance of the selected features and interpret the ML models. Results: Fifty-five (17.97%) acromegaly patients met the criteria for DR, and five features (post-1w rGH, post-1w nGH, post-6m rGH, post-6m IGF-1, and post-6m nGH) were significantly associated with DR in both training and test datasets. After RFE feature selection, the XGboost model, which comprised the fifteen important features, had the greatest discriminatory ability (AUC=0.8349, sensitivity=0.8889, Youden’s index=0.6842). The XGboost model showed good discrimination ability, and provided significantly better estimates of DR of patients with acromegaly compared with using only the Knosp grade. The results obtained from permutation importance, SHAP, and the LIME algorithms showed that post-6m IGF-1 is the most important feature in XGboost algorithm prediction, and showed the reliability and clinical practicability of XGboost model in DR prediction. Conclusions: ML-based models can serve as an effective non-invasive approach to predicting DR, and could aid in determining individual treatment and follow-up strategies for acromegaly patients who have not achieved remission within 6 months of surgery.